Evolução da assistência materno-infantil na cidade de São Paulo (1984-1996) Secular trends in maternal and child health care in S. Paulo city, Brazil(1984-1996) - Carlos Augusto Monteiro; Ivan França Júnior; Wolney Lisboa Conde (Universidade de São Paulo, 2000)
OBJETIVO: Descrever a evolução da assistência materno-infantil, com base nas informações extraídas de dois inquéritos domiciliares realizados nos anos de 1984/85 e de 1995/96, na cidade de São Paulo, SP. MÉTODOS: Foram estudadas amostras probabilísticas da população entre zero e 59 meses de idade: 1.016 crianças em 1984/85 e 1.280 crianças em 1995/96. Três componentes da assistência materno-infantil foram investigados: assistência pré-natal, assistência ao parto e ao recém-nascido e assistência de puericultura. RESULTADOS: Aspectos favoráveis da evolução da assistência materno-infantil na cidade de São Paulo foram a manutenção da cobertura universal da assistência hospitalar ao parto, a expansão substancial do alojamento conjunto mãe-filho na maternidade, o aumento no número de consultas de puericultura no primeiro ano de vida e, sobretudo, a universalização da cobertura das vacinas BCG, tríplice e anti-sarampo. Aspectos desfavoráveis foram o progresso muito modesto e claramente insuficiente da assistência pré-natal, a manutenção de quase 50% de cesarianas e a não expansão da puericultura após o primeiro ano de vida. CONCLUSÕES: Estimativas sobre a evolução da assistência materno-infantil no conjunto das áreas urbanas do País em período semelhante confirma e acentua o desempenho insatisfatório da assistência pré-natal na cidade de São Paulo. Comparações favoráveis a São Paulo são registradas apenas quanto a cobertura vacinal. A influência que mudanças na assistência materno-infantil podem ter exercido sobre a evolução de diferentes indicadores do estado de saúde das crianças da cidade é examinada em artigos subseqüentes. OBJECTIVE: Two consecutive household surveys undertaken in mid-80s and mid-90s in the city of S. Paulo, Brazil, made possible to establish time trends of several child health determinants and indicators as well as to analyse the relationships among them. The study intends to report trends in maternal and child health care. METHODS: Random samples of the population aged from zero to 59 months were studied: 1,016 children in the period of 1984-85 and 1,280 children in 1995-96. Both surveys investigated three components of maternal and child health care: prenatal care, delivery and newborn care and routine health care provided to children up to five years of age (including development follow-up and vaccination). RESULTS: Favourable changes seen in the period between the two surveys were the continuing universal birth coverage, significant increase in rooming-in in maternity hospitals and the number of routine visits for babies in their first year of life and, particularly, the universal outreach of the DPT, measles and tuberculosis vaccinations. Unfavourable trends were seen regarding the slight and clearly insufficient growth of prenatal care, the still high percentage (of near 50%) of cesarean sections, and the limited routine visits for children after their first year of age. CONCLUSIONS: Estimates in the same period for the outreach of maternal and child health care in other urban areas of Brazil reinforce the unsatisfactory trends of the prenatal care in S. Paulo. Favourable comparisons are only seen regarding the outreach of child vaccination. The influence that changes in the maternal and child health care provided in the city may have exerted on several child health indicators is examined in subsequent articles.